Las prácticas gimnásticas y la condición física en estudiantes de 10mo año de la Unidad Educativa Lauro Damerval Ayora de la ciudad de Loja, 2023. - Paredes Jiménez, Roris Acxel (2024)
In the context of Ecuadorian education, the incorporation of gymnastic practices in the curricular block faces various challenges, in which teachers and students are immersed; One of these is to allow the discipline of gymnastics to be part of the planning in the subject of Physical Education, and this leads to the adaptation of appropriate spaces for its execution; thus, impacting the achievement and improvement of teaching-learning. Gymnastics practices are presented as an alternative to improve the physical condition of students; In this sense, the objective of this research lies in analyzing the impact of gymnastic practices on the physical condition of tenth-year students of Basic General Education of the Lauro Damerval Ayora Educational Unit. The present work is a type of descriptive and documentary research with a mixed approach; Its design is quasi- experimental with the support of deductive, inductive, analytical, and statistical methods; The results emerge from the application of the pre-test and post-test where the strength, flexibility and resistance of the students are measured, in a before and after. From the results obtained through the instruments, a plan of gymnastic practices was implemented that contributed to the improvement of the physical condition of the students, evidencing the conditional capabilities; thus concluding that gymnastic practices play a favorable role in improving physical condition, generating greater motivation, and effectively prepare students to carry out any physical activity within the framework of the subject. Keywords: gymnastic practices, physical condition, conditional abilities, flexibility, strength, resistance.